The Multi-modality Cardiac Imaging Approach to Cardiac Sarcoidosis - Ricci, Fabrizio; Mantini, Cesare; Grigoratos, Chrysanthos; Bianco, Francesco; Bucciarelli, Valentina; Tana, Claudio; Mastrodicasa, Domenico; Caulo, Massimo; Donato Aquaro, Giovanni; Raffaele Cotroneo, Antonio; Gallina, Sabina (Current Medical Imaging, 2019)
Background: Sarcoidosis is a multisystem granulomatous disease with a neglected but high prevalence of life-threatening cardiac involvement. Discussion: The clinical presentation of Cardiac Sarcoidosis (CS) depends upon the location and extent of the granulomatous inflammation, with left ventricular free wall the most common location followed by interventricular septum. The lack of a diagnostic gold standard and the unpredictable risk of sudden cardiac death pose serious challenges for the validation of accurate and effective screening test and the management of the disease. In the last few years advanced cardiac imaging modalities such as Cardiac Magnetic Resonance (CMR) and Positron Emission Tomography (PET) have significantly improved our knowledge and understanding of CS, and have also contributed in risk stratification, assessment of inflammatory activity and therapeutic monitoring of the disease. Conclusion: In this review, we will discuss the state of the art in the diagnosis of CS focusing on the role and importance of multi-modality cardiac imaging.
Keywords: echocardiography